Journal: Safety Talk / Value of a Good Hearing Loss Prevention Program (International Society of Explosives Engineers, 2006)
When a company has an effective hearing loss prevention program, everyone wins-the employers, the employees, and the safety and health professionals who implement the program. This guidebook is not about minimal programs that meet only the letter of the law. It is concerned with programs that are effective as well as efficient: those optimizing program elements that succeed in preventing hearing loss in a practical and cost effective manner.